A compact configuration of semicircular metasurface loaded slot antenna for beam steering application. Issue 2 (31st August 2018) - Katare, Kranti Kumar; Chandravanshi, Sandhya; Biswas, Animesh; Akhtar, M. Jaleel
Abstract: In this article, a compact beam steering antenna configuration is presented. The proposed structure comprises a semicircular radially gradient metasurface (SCRGM) and a slot antenna. This metasurface (MS) with the dimensions of 3.17 λ 0 2 covers only half of the antenna aperture by placing it at a height of 0.16 λ 0 from the slot antenna. The SCRGM is made up of four different semicircular regions, which introduce progressive phase delay to the impinging spherical electromagnetic waves from the slot antenna. The placement of the SCRGM tilts the main beam by 30° away from the normal direction. Furthermore, in‐plane movement (rotation and translation) of the SCRGM facilitates beam steering in the elevation plane (E‐plane) with the total scanning range of 60°. Moreover, in simulation, two SCRGMs are placed at both sides of antenna aperture to independently control the beam directions in both upper and lower hemispheres of the slot antenna. Due to the symmetry of the slot antenna, only one SCRGM is tested during the measurement process and the same outcome is expected for the other MS. Considerably small volume (0.50 λ 0 3 ) of the structure revealed compact antenna configuration. Moreover, independent control of the beam directions in both of the hemispheres makes proposed antenna a suitable candidate for various applications.